Innovations in MXene composite engineering for hydrogen energy storage: recent advances, challenges, and future prospects - Hossain, M. A.Motalib; Hannan, M. A.; Tiong, Sieh Kiong; Ker, Pin Jern; Farid, M. H.; Jang, Gilsoo (Elsevier B.V., 2026)
Hydrogen (H2) energy storage remains yet another challenging aspect to be tackled in the progress of H2-based energy systems. However, MXenes composite have drawn considerable interest in H2 storage due to their tunable huge surface area, conductivity, intercalation ability, and variety of compositions. By tunable interlayer spacing and transition metal elements, MXenes originally allows fine adjustment in both chemical and physical of the H2 adsorption energy and so, they are being studied as H2 storage materials. This review tries to cover in very exhaustive terms the state of the art in the MXene composites for the H2 storage in terms of material design, synthesis routes, and performance improvements. Various engineering techniques for enhancing H2 adsorption and desorption kinetics have been identified, such as doping with heteroatoms, hybridization with metal hydrides and porous materials, and surface functionalization. The review also describes computational approaches that can be employed to predict efficient MXene behaviors for H2 storage. Moreover, a discussion on long-term stability, scale-up, and manufacturing challenges is provided. The future research outlook toward optimization of MXene-based composites is thereafter reviewed. Hence, this review provides an insight into the key issues surrounding MXenes for the next-generation H2 storage technologies in sustainable energy solutions.